Ethical Ideology and the Ethical Judgments of Marketing Professionals - Barnett, Tim (Journal of business ethics, 1998)
The present study extends the study of individuals' ethical ideology withinthe context of marketing ethics issues. A national sample of marketing professionals participated. Respondents' ethical ideologies were classified as absolutists, situationists, exceptionists, or subjectivists using the Ethical Position Questionnaire (Forsyth, 1980). Respondents then answered questions about three ethically ambiguous situations common to marketing and sales. The results indicated that marketers' ethical judgments about the situations differed based on their ethical ideology, with absolutists rating the actions as most unethical. The findings are consistent with those of two earlier studies that utilized samples of business students (Barnett et al., 1994, 1995). The results suggest that personal moral philosophy is an important influence on ethical decision making that should be considered in empirical studies of business ethics. The results also support the utility of the Ethical Position Questionnaire (Forsyth, 1980) as a means for researchers and practitioners to assess individuals' ethical ideology.